ФОРМУВАННЯ ПРОФЕСІЙНОЇ ІНШОМОВНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ФАХІВЦЯ ЦИВІЛЬНОГО ЗАХИСТУ НА ЗАСАДАХ КУЛЬТУРОЛОГІЧНОГО ПІДХОДУ - Вовчаста, Наталія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті висвітлено доцільність формування професійної іншомовної підготовки майбутнього фахівця цивільного захисту на засадах культурологічного підходу. Обґрунтовано педагогічні умови якісної іншомовної професійної підготовки майбутніх фахівців цивільного захисту (виявлення чинників впливу, зумовлених специфікою професійної діяльності; взаємодія спеціальної та іншомовної складових; неперервність іншомовної професійної підготовки; розвиток активної професійної позиції на основі розвитку комунікативної складової; забезпечення мотивації та розвиток позитивного ставлення до іншомовної професійної підготовки тощо). В статье освещены целесообразность формирования профессиональной иноязычной подготовки будущего специалиста гражданской защиты на основе культурологического подхода. Обоснованы педагогические условия качественной иноязычной профессиональной подготовки будущих специалистов гражданской защиты (выявление факторов влияния, обусловленных спецификой профессиональной деятельности; взаимодействие специального и иноязычной составляющих; непрерывность иноязычной профессиональной подготовки, развитие активной профессиональной позиции на основе развития коммуникативной составляющей, обеспечение мотивации и развитие позитивного отношения к иноязычной профессиональной подготовки и т.д.). The expediency of formation of professional foreign language training of future civil defense specialist based on cultural approach as the essential component of humanistic pedagogy is explained in the article. It is shown that at foreign communication culture on the level of personal quality of specialist determines the degree of his professional maturity. Pedagogical conditions providing of the qualitative foreign language training of future civil defense specialist on the basis of cultural approach (identifying and taking into account the factors of influence due to specific professional activity of civil defense specialist, the interaction of special and foreign language components as important factor in the training of specialist, life-long of foreign language training, the development of active professional position through the development of communicative component, ensuring the formation of motivation of foreign language training and developing a positive attitude to the language, understanding of own needs and opportunities in the foreign language training, etc.).